Growth performance of tilapia fingerling in cage in ponds managed by Adivasi households: An assessment through length-weight relationship (Journal of the Bangladesh Agricultural University, 2012)
This study was conducted to assess the growth performances of cage reared GIFT strain of tilapia (Oreochromis niloticus) fingerling using length-weight (LW) relationship technique. Along with this, condition factor (K) of fish and   pond water quality parameters were also brought under this study to have broader understanding. For LW  relationship and K, a sample size of 120 fingerlings was made from randomly selected three different cages in a pond  at Tarala village in Kaharole Upazila of Dinajpur District, Bangladesh. The length-weight relationship of tilapia  fingerlings reared in cages managed by Adivasi people was significant. The value of correlation coefficient (r) and the coefficient of determination (r2) were 0.97 and 0.94 respectively. This suggests that growth of tilapia from fry to  fingerling was normal in cages. The condition factor of different size group of fish was almost closed to 2, indicating  fish health as satisfactory. All the water quality parameters including temperature, transparency, dissolved oxygen,ammonia-nitrogen, phosphate-phosphorus, nitrate-nitrogen and pH were within suitable range both in cages and  outside the cage in pond. About 5 phyla and 25 genera of phytoplankton from Bacillariophyceae, Cyanophyceae, Chlorophyceae, Euglenophyceae and Rhodophyceae groups and one phylum and 5 genera of zooplankton from Rotifera group were found in cage installed in ponds. These all indicate the growth of tilapia fingerling in cages was satisfactory which was technically sound for landless adivasi households.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12107   J. Bangladesh Agril. Univ. 10(1): 149155, 2012